Conducting research on Makers with Future Science Leaders: experiences from a museum enrichment program - Milne, Andrew P. (Interaction Design for Children, 2013)
Future Science Leaders (FSL) is a high school enrichment program run out of a science museum in Vancouver, Canada. FSL uses project and problem-based learning to teach science and technology process skills. This paper describes successes and challenges from the first two years of FSL, and two ongoing research projects being done in connection with the program. The first study involves interviews and a survey of local "Makers" (a broad community of do-it-yourself enthusiasts), and seeks to identify commonalities in their 'Maker process'. The second study uses interviews and text analysis to explore FSL students' attitudes towards science.
Keywords: DIY; Riecke; Riecke_2013; andrew-milne; conferencePapers